Dynamics of one of the largest Quaternary explosive eruptions in the Andes: the ca. 29 ka Campo de la Piedra Pómez VEI ≥ 6 caldera-forming eruption, NW Argentina - Báez, Walter; Silva, Shanaka de; Cirer, Mercedes; Bertea, Esteban; Constantinescu, Robert; Danišík, Martin; Schmitt, Axel Karl; Ramos, Frank C. (Bulletin of volcanology, 2025)
Large explosive volcanic eruptions (Volcanic Explosivity Index ≥ 6) have the potential to profoundly impact modern society. Databases that encompass information on age, size, dynamics, and geological context of large eruptions are essential for devising effective long-term strategies for hazard and risk assessment. A critical limitation of these databases is the underreporting of events, particularly of those that occurred in remote regions like the southern edge of the Central Volcanic Zone of the Andes (24-27°S). In this study, we provide the first lithofacies description of the proximal and distal fall deposits linked to a previously overlooked eruption in this region, the Campo de la Piedra Pómez caldera-forming eruption from the Cerro Blanco Volcanic Complex (NW Argentina). Importantly, a zircon double-dating age of 28.9 ± 3.2 ka (2σ) for the Campo de la Piedra Pómez eruption is significantly younger than a previously reported 40Ar/39Ar sanidine age. In addition, a new (U-Th)/He age for the Barranca Blanca Ignimbrite indicates that it is significantly older and unrelated to the Cerro Blanco Volcanic Complex, clarifying a long-standing stratigraphic question. Major and trace element compositions of bulk rock and glass allow for a reliable regional correlation of proximal and distal fall deposits, and a clear geochemical distinction of the Campo de la Piedra Pómez eruption from other potential sources with similar compositions. Using inverse modeling of tephra dispersion, we estimate a minimum fall deposit volume of ~ 25.6 ± 5.6 km3. Adding this to the previous estimate of 17.2 km3 for the ignimbrite, the minimum bulk tephra erupted during the Campo de la Piedra Pómez eruption is now estimated at 42.7 km3 (~ 17.5 km3 Dense Rock Equivalent). The dynamics of the Campo de la Piedra Pómez eruption have been reconstructed from field-based data including facies analysis, componentry, and maximum size distribution of lithic clasts. The eruption started with a sustained Plinian phase characterized by a high discharge rate (108 - 109 kg/s) and an eruptive plume of ~ 35-40 km above the vent. Partial plume collapse then generated high-mobility pyroclastic density currents. The onset of caldera collapse triggered the transition to a mixed eruptive style, including the development of pyroclastic fountaining (boiling-over) from fissure-like vents accompanied by substantial pyroclastic density currents, and coeval convective Plinian plume activity from a spatially separated narrow vent. As the eruption progressed, fissure-like vents expanded, entirely halting the convective Plinian plume. Despite the huge volume erupted, the Campo de la Piedra Pómez eruption produced only an incipient collapse structure with limited subsidence.
Online veröffentlicht: 21. August 2025
Gesehen am 12.01.2026